2021
DOI: 10.1111/labr.12189
|View full text |Cite
|
Sign up to set email alerts
|

Shifting the Training Choice Decision to the Jobseeker—The Slovak Experience

Abstract: We describe a reform in the allocation of training to unemployed jobseekers in Slovakia. Under the REPAS reform, unemployed jobseekers choose a specialization and training provider. This shift in responsibility from the caseworker to the client is comparable to the introduction of training vouchers under the German HARTZ I reform. Benefiting from research available on the German case, we first estimate the positive employment effects of training participation separately for the pre‐REPAS and REPAS periods. Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This paper discussed the politically relevant issue of whether chosen training could allocate the unemployed better to appropriate training programs, potentially leading to improved program effects. Researchers in other EU countries, including Eastern European countries, also addressed this topic (Rinne et al, 2013;Stefanik, 2021;Madoń et al, 2021). These analyses generally argued that involvement of the unemployed in program selection is in some ways positive for program effects.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This paper discussed the politically relevant issue of whether chosen training could allocate the unemployed better to appropriate training programs, potentially leading to improved program effects. Researchers in other EU countries, including Eastern European countries, also addressed this topic (Rinne et al, 2013;Stefanik, 2021;Madoń et al, 2021). These analyses generally argued that involvement of the unemployed in program selection is in some ways positive for program effects.…”
Section: Discussionmentioning
confidence: 99%
“…While short-term effects were higher after the reform (more pronounced locking-in effect before the reform), similar effects were found at the end of the observed period of 22-27 months (after the training). While Rinne et al (2013) found the positive reform effect only for skilled individuals, Stefanik (2021) provided a contrasting example, with the low-skilled (ISCED 0-2) participants benefiting from training par-ticipation slightly more than high-skilled (ISCED 5-6) participants, especially in the longer run, and no reform effect. Madoń et al (2021) found a difference between chosen and standard type of training for onthe-job training, but not for the classroom training.…”
Section: Previous Empirical Evidence On the Impact Of Training Programsmentioning
confidence: 93%
See 3 more Smart Citations